Morphological and molecular identification of all developmental stages of four whitefly species (Hemiptera: Aleyrodidae) commonly intercepted in quarantine - Malumphy, Christopher; Walsh, Katherine; Suarez, M. Belen; Collins, Dominique W.; Boonham, Niel (Zootaxa, 2009)
Whiteflies are inadvertently, but commonly, transported in international plant trade. Rapid, accurate identification is the essential first step when such insects are intercepted by quarantine authorities. Whitefly taxonomy, and identification, is almost entirely based on the fourth-larval instar or puparium, but often only the eggs, early larval instars or adults are detected. Morphological descriptions of the egg, first three larval stages and adult are presented for four species commonly detected in trade, Bemisia afer (Priesner & Hosny), B. tabaci (Gennadius), Trialeurodes ricini (Misra) and Trialeurodes vaporariorum (Westwood). Morphological characters are provided that enable most life stage/species combinations in these four species to be distinguished. The structure of the antenna is a reliable and simple character for separating the four larval instars. Phenotypic plasticity, previously only reported in the puparial stage, also occurs in the second and third-larval instars. Where morphological separation of two species is sometimes inconclusive, or impossible, identification can be achieved using four real-time PCR assays, designed and validated to distinguish between the four species. The assays are generic in their set-up and can be multiplexed to form two reactions allowing discrimination of B. afer and B. tabaci in one well, and T. ricini and T. vaporariorum in another.